Boost Buck Converter Based on Fuzzy Logic for Voltage Stabilizer - Mohammad Alfian Mudzakir; Arief Marwanto; Suryani Alifah (Universitas Islam Sultan Agung, 2022)
The wind turbine generator used for charging the battery produces an unstable electrical voltage, this is caused by the wind speed on the highway that varies. As a result of the instability of the electrical voltage, the energy storage charging process is not optimal. To deal with these problems, voltage stabilization is carried out using a boost buck converter to maximize the use of electrical energy generated from the wind turbine generator. This study discusses about a prototype voltage stabilizer for battery charging using a boost buck converter circuit. Implemented a comparison of two different techniques, including the application of fuzzy Mamdani logic control with PID using Ziegler-Nichols to minimize the value of settling time, percentage of overshoot, steady state error, and maximum voltage ripple. The results show that application of fuzzy Mamdani logic control is more effective than the application of PID using Ziegler-Nichols. In the study, it was found that the effectiveness of adding a charging circuit protection system and monitoring system did not exist in previous studies.